A small molecule screen identifies novel inhibitors of mechanosensory nematocyst discharge in Hydra - Hofmann, Diana; Garg, Niharika; Grässle, Simone; Vanderheiden, Sylvia; Bergheim, Bruno Gideon; Bräse, Stefan; Jung, Nicole; Özbek, Suat (Scientific reports, 2021)
Cnidarians are characterized by the possession of stinging organelles, called nematocysts, which they use for prey capture and defense. Nematocyst discharge is controlled by a mechanosensory apparatus with analogies to vertebrate hair cells. Members of the transient receptor potential (TRPN) ion channel family are supposed to be involved in the transduction of the mechanical stimulus. A small molecule screen was performed to identify compounds that affect nematocyst discharge in Hydra. We identified several [2.2]paracyclophanes that cause inhibition of nematocyst discharge in the low micro-molar range. Further structure-activity analyses within the compound class of [2.2] paracyclophanes showed common features that are required for the inhibitory activity of the [2.2] paracyclophane core motif. This study demonstrates that Hydra can serve as a model for small molecule screens targeting the mechanosensory apparatus in native tissues.